Tasks to promote argumentation in math class based on Dynamic Geometry Software - Ríos Cuesta, Wilmer (Rastros Rostros, 2023)
Purpose: The tasks proposed to students have an impact on the cognitive activity they develop and on the construction of concepts and joint meanings. In this article we propose two tasks to promote interactivity in class mediated by argumentation processes with the use of GeoGebra. Description: Dynamic geometry environments allow students to experiment with different types of semiotic representation to mediate the cognitive activity they develop. Although some studies suggest that these environments decrease the cognitive load, it is recognized in the literature the impact that this type of systems generate in school learning, such as their use promotes the development of strategies to extend the problem or explore cases that allow students to generalize on a hypothesis or conjecture. In this sense, the importance of entrainment and of the concepts, definitions and fundamental topics of Euclidean geometry that are necessary for the constructions of the models that are tested is highlighted. Point of view: The teacher's mediation and the presentation of significantly rich and challenging tasks allow generating moments of interactivity where the teacher's actions are articulated with those of the students around the task. Conclusions: it is important for teachers to design activities that promote argumentation spaces in class as an opportunity to learn mathematics, since it allows confronting different points of view and mediating in the construction of meanings.
Keywords: argumentation; modeling; social interaction; interactivity; task design